INFLUENCE OF A NEW COMPLEX MINERAL FERTILIZER CALLED NITROAMOFOSKA-M ON THE YIELD AND QUALITY OF BROCCOLI - Dydiv, О.; Dydiv , І.; Zanevych-Baikovska, А.; Franchuk, Й.; Rosa, Р. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
The study aimed to examine the effect of different rates of a new complex mineral fertilizer called Nitroamophoska-M on the yield and biochemical composition of broccoli, specifically the hybrid Koros F1. The study took place in the Western Forest-Steppe of Ukraine on dark gray podzolic loamy soils. The hybrid of broccoli Koros F1 was chosen as the subject of the research. The scheme of the experiment included six versions: 1) Control (without fertilizers); 2) Ammonium nitrate (175 kg/ha) – background; 3) Background + Nitroammophoska-M (200 kg/ha); 4) Background + Nitroammophoska-M (400 kg/ha); 5) Background + Nitroammophoska-M (600 kg/ha); 6) Background + Nitroammophoska-M (800 kg/ha). The average results of the two-year research showed that a large diameter (16 and 18 cm) and weight of heads (754 and 836 g) were obtained on the versions: Background + Nitroammophoska-M (400 kg/ha) and Background + Nitroammophoska-M (600 kg/ha), while in the control version (without fertilizers) these figures were the lowest and amounted to 12 cm and 422 g, respectively. Using the seedling growing method and applying Nitroammophoska-M fertilizers at the rate of 400 kg/ha and 600 kg/ha, the researchers obtained a high yield of broccoli heads (30.8 and 32.5 t/ha), exceeding the control by 9.4 and 11.1 t/ha, respectively. The results showed that the use of Nitroammophoska-M fertilizers at the rate of 800 kg/ha did not significantly increase the yield compared to version 5 with the application of fertilizers at the rate of 600 kg/ha. Nitroamophoska-M fertilizer improved the quality of broccoli heads. The highest content of dry matter (11.3 %), total sugar (5.0 %), and ascorbic acid (82.4 mg/100 g) were marked in version 5 where Nitroammophoska-M was applied at the rate of 600 kg/ha. The content of nitrate nitrogen in all versions of the experiment did not exceed the maximum allowable concentration (400 mg/kg of wet weight). Based on the results, it is proposed to apply Nitroamophoska-M fertilizer at the rate of 600 kg/ha on the background of ammonium nitrate (175 kg/ha) to obtain a high yield with good quality broccoli heads of the hybrid Koros F1. The seedling growing method is also recommended for broccoli cultivation on dark gray podzolic soils in the Western Forest-Steppe of Ukraine.